FROM HISTORY OF THE POLISH THEATER IN STANISLAVIV (1933-1939) - Tsivkach, O. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Problems, which touch the problem of creation, activity, repertoire policy and functioning of the Polish professional theater in Stanislaviv (Ivano-Frankivs’k) under the direction of Zuzanna Lozinsky in a period intermilitary 20 ages, are explored in the article, the questions of composition of theatrical troupe are examined, selection of repertoire and departure activity of theater.